1. Simplifying

a + -3 + 5a + -2 = 0

Reorder the terms:

-3 + -2 + a + 5a = 0

Combine like terms: -3 + -2 = -5

-5 + a + 5a = 0

Combine like terms: a + 5a = 6a

-5 + 6a = 0

Solving

-5 + 6a = 0

Move all terms containing a to the left, all other terms to the right.

Add '5' to each side of the equation.

-5 + 5 + 6a = 0 + 5

Combine like terms: -5 + 5 = 0

0 + 6a = 0 + 5

6a = 0 + 5

Combine like terms: 0 + 5 = 5

6a = 5

Divide each side by '6'.

a = 0.8333333333

Simplifying

a = 0.8333333333

2. reciprocal of(-1) / 5 = -0.

3. 0.5

I relooked at it. Is this all correct?